Chemical constituents and pharmacological effects from different parts of grape Vitis vinifera L. (Vitaceae): A review - Ha, Ly Hong Huong; Trinh, Tran Trung; Ngoc, Vo Thi Bich (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
Vitis vinifera fruit (grape) possesses phenolic compounds, flavonoids, and stilbenes. Active substances have recently been found in the whole fruit, flesh, seed, skin, pomace, leaf and tendril, and root of grapes. This article reviews the active constituents of different parts of V. vinifera and their pharmacological effects, including antioxidant, anticancer, anti-inflammatory, antidiabetic, hepatoprotective, cardioprotective, and neuroprotective properties. Intriguingly, the cultivars and extraction technology play a pivotal role in determining individual extracts' biological activity.